Serum α-Carotene, but Not Other Antioxidants, Is Positively Associated with Muscle Strength in Older Adults: NHANES 2001–2002 - Renata R. Bruno; Fernanda C. Rosa; Paula C. Nahas; Flávia M. S. de Branco; Erick P. de Oliveira (Antioxidants, 2022)
Aging is associated with an increased reactive oxygen species that can decrease muscle strength. Thus, antioxidant substances could be positively associated with muscle strength in older adults. To investigate the association between serum antioxidants and muscle strength in older adults. A cross-sectional study evaluating 1172 individuals (627 men and 545 women), aged 50 to 85 years from NHANES 2001–2002, was performed. Carotenoids (α-carotene, trans-β-carotene, cis-β-carotene, β-cryptoxanthin, lutein/zeaxanthin combination, trans-lycopene), vitamin E, and retinol were analyzed via the high-performance liquid chromatography method. Muscle strength was evaluated by the isokinetic knee extension test. Linear regression was performed to evaluate the association between tertiles of serum antioxidant levels and strength, adjusted for confounders (energy and protein intake, body mass index, sex, age, C-reactive protein, uric acid, race/ethnicity, marital status, annual household income, educational level, physical activity, smoking, hypertension, arthritis, and diabetes). Alpha-carotene levels (p-trend = 0.027) were positively associated with muscle strength. However, serum vitamin E, trans-β-carotene, cis-β-carotene, β-cryptoxanthin, carotenoids, and retinol levels were not associated with strength. Serum α-carotene, but not other antioxidants, was positively associated with muscle strength in older adults.